2022
DOI: 10.1007/s12144-022-03755-y
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety in adolescents and young adults from the general population: an epidemiological characterization of fear and avoidance in different social situations

Abstract: Social Anxiety Disorder (SAD) and, more generally, social fears are common in young people. Although avoidance behaviors are known to be an important maintaining factor of social anxiety, little is known about the severity and occurrence of avoidance behaviors in young people from the general population, hampering approaches for early identification and intervention. Symptoms, syndromes, and diagnoses of DSM-5 mental disorders including SAD were assessed in a random population-based sample of 14-21-year-olds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…As expected, co-morbidity was rampant, and the majority of adolescents with SAD (n=14, 58.3%) received at least one other categorical diagnosis (Koyuncu et al, 2019;Lahey et al, 2022;Tiego et al, 2023). GAD (n=12, 50.0%) and MDD (n=8, 33.3%) were the most common co-morbidities, in broad accord with recent adolescent epidemiology studies (Ernst et al, 2023;Jystad et al, 2021).…”
Section: Participants and Eligibility Criteriasupporting
confidence: 80%
See 2 more Smart Citations
“…As expected, co-morbidity was rampant, and the majority of adolescents with SAD (n=14, 58.3%) received at least one other categorical diagnosis (Koyuncu et al, 2019;Lahey et al, 2022;Tiego et al, 2023). GAD (n=12, 50.0%) and MDD (n=8, 33.3%) were the most common co-morbidities, in broad accord with recent adolescent epidemiology studies (Ernst et al, 2023;Jystad et al, 2021).…”
Section: Participants and Eligibility Criteriasupporting
confidence: 80%
“…Social anxiety lies on a continuum and, when extreme, can be devastating, with functional impairment evident in many individuals who do not meet full diagnostic criteria ( Fehm et al, 2008 ; Hyett & McEvoy, 2018 ; Katzelnick et al, 2001 ; Kessler, 2003 ; Lipsitz & Schneier, 2000 ; Merikangas et al, 2002 ; Schneier et al, 2002 ). Social anxiety disorder (SAD) is among the most common psychiatric illnesses (lifetime prevalence: ∼13%), typically emerges in adolescence, and confers heightened risk for a variety of other developmental, academic, and psychiatric problems, including co-morbid internalizing disorders and substance misuse ( Angst et al, 2016 ; Beesdo-Baum & Knappe, 2012 ; Ernst et al, 2023 ; Gregory et al, 2007 ; Hyett & McEvoy, 2018 ; Jystad et al, 2021 ; Kessler et al, 2012 ; Koyuncu et al, 2019 ; Mathew et al, 2011 ; Schneier et al, 1992 ; Stein et al, 2017 ). Existing treatments are inconsistently effective or associated with significant adverse effects, underscoring the urgency of developing a more complete understanding of the neural systems governing social anxiety in the first decades of life ( Batelaan et al, 2017 ; Beidel et al, 2019 ; Cuijpers et al, 2024 ; Evans et al, 2021 ; James et al, 2020 ; Rapee et al, 2023 ; Scholten et al, 2016 ; Scholten et al, 2013 ; Singewald et al, 2023 ; Spinhoven et al, 2016 ; Strawn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the findings of this study are slightly different from those stated in research by Ernst et al, who found that in the situational group, the social situations that most often cause anxiety and avoidance are exam situations, especially oral exams and speaking or performing in front of others. Whereas in the group with lifelong social anxiety disorder, the social condition that causes the most anxiety is having a party, and the most frequent avoidance is talking to almost unknown people (18). But the findings from this study may differ depending on the experiences experienced by the respondents.…”
Section: Discussionmentioning
confidence: 53%
“…Social avoidance is crucial in social anxiety and social phobia, serving as a major factor in maintaining anxiety [47]. Experimental investigations indicate that social anxiety and social avoidance often emerge in early adolescence, and preventive or early intervention measures significantly reduce their occurrence [48]. The onset of social anxiety in adolescents may be partly attributed to an increase in avoiding social situations during this period [49] and familial genetic factors [50].…”
Section: Hypothesis 4 (H4) Self-disclosure Negatively Affects Social ...mentioning
confidence: 99%